2019
DOI: 10.21203/rs.2.10826/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial Urinary Tract Infection among Adult Renal Transplant Recipients at St. Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia

Abstract: Background: Despite significant advances in surgical techniques, immunosuppression protocols follow up periods and antimicrobial stewardship in modern medicine; post-renal transplantation urinary tract infection remained a major public health problem globally. This multiple serious squeal includes asymptomatic bacteriuria, cystitis and pyelonephritis. Among these, the bacterial origin of infection complications accounts for the most significant clinical, socio-economic impacts in many countries of the world. T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(57 reference statements)
1
2
0
Order By: Relevance
“…This finding represents the high prevalence of MDR uropathogens among renal transplantation recipients. In Kiros et al study, multidrug resistance was reported in 82% of the isolates among renal transplant recipients (30). In the study of Khosravi et al (31) , the most common resistance was reported against cefixime, cephalothin, and TMP/SMX, which was consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…This finding represents the high prevalence of MDR uropathogens among renal transplantation recipients. In Kiros et al study, multidrug resistance was reported in 82% of the isolates among renal transplant recipients (30). In the study of Khosravi et al (31) , the most common resistance was reported against cefixime, cephalothin, and TMP/SMX, which was consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Since there was a high chance of contamination, urine samples collected using a collecting bag or pad were disregarded [27]. Ten, 5-10 ml of urine samples was taken from each research subject using sterile, screw-capped, wide-mouth containers and labeled with the patient's medical identifcation number [28]. Te urine sample was subsequently subjected to bacteriological testing using standard operating procedures [7,23,29].…”
Section: Specimen Collection Handling Processing Andmentioning
confidence: 99%
“…Isolate identifcation to species level was done by their colony characteristics (size, shape, turbidity, and hemolysis), Gram staining, and pattern of biochemical profles. Te biochemical test was conducted to assess indole production, H2S production, lactose fermentation in TSI agar, citrate utilization, motility test, urease test, bile solubility, and lysine utilization in lysine decarboxylase( LDC) agar [28]. An oxidase test was also performed for other Gram-negative rods.…”
Section: Urinementioning
confidence: 99%